The complete chloroplast genome sequence of Veratrum nigrum L. - Wen-Xiao Men; Yue-Yue Song; Che Bian; He-Fei Xue; Yan-Ping Xing; Liang Xu; Ming Xie; Ting-Guo Kang (Mitochondrial DNA. Part B. Resources, 2022)
The complete chloroplast genome of an important medicinal plant, Veratrum nigrum Linnaeus, was sequenced. The entire circular genome is 151,580 bp in length, with 37.7% GC contents. The genome has a large single-copy (LSC) region with a length of 81,806 bp, a small single-copy (SSC) region with a length of 17,472 bp, and two inverted repeat regions (IRs) with a length of 26,151 bp. It harbored 131 genes, including 85 protein coding genes, 38 tRNA genes, and eight rRNA genes. Phylogenetic analysis suggested V. nigrum formed a monophyletic clade with relatively short genetic distance to Veratrum oxysepalum and Veratrum taliense. This study will provide theoretical basis for further study on plant genetics phylogenetic research.